Réponses

2014-04-10T11:14:57+02:00
Bonjour,

a) f(x) = (x - 1)(x + 5)
          = x² + 5x - x - 5 
          = x² + 4x - 5
          = (x² + 4x + 4) - 4 - 5
          = (x + 2)² - 9
 
 g(x) = 2x² - 8x + 16
        = 2(x² - 4x + 8)
        = 2[(x² - 4x + 4) - 4 + 8]
        = 2[(x - 2)² + 4]
        = 2(x - 2)² + 8

    h(x) = x² - 18x + 81
           = (x - 9)²
  • Utilisateur Brainly
2014-04-10T13:08:59+02:00
forme canonique de :
 f(x)=(x-1)(x+5)
     =x²+4x-5
     =(x+2)²-9

 g(x)=2x²-8x+16  
     =2(x²-4x)+16
     =2(x-2)²+8

 h(x)=x²-18x+81
       =(x-9)²